2021
DOI: 10.18510/hssr.2021.93104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Current Account Gaps on Inflation in South Asian Countries

Abstract: Purpose of the study: The current study estimated the impact of current account gaps (CAGAP) on inflation in South Asian countries, namely, Pakistan, Bangladesh, India, Nepal, and Sri Lanka. Methodology: CAGAP is estimated through macroeconomic fundamentals by applying panel time series data methodology from 1990 to 2018. We adopted the bias-corrected least square dummy variable (LSDVC) estimation technique for the time series macro and dynamic panel to find the impact of CAGAP on inflation. Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the type of music and its characteristics can also affect cognitive performance. For example, fast and loud music can impair reading comprehension, while baroque instrumental music is excellent for improving attention and reasoning (Ahmad & Rana, 2015;Nadon et al, 2021). Moreover, familiar music is also associated with increased enjoyment and performance on cognitive tasks (Ahmad & Rana, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the type of music and its characteristics can also affect cognitive performance. For example, fast and loud music can impair reading comprehension, while baroque instrumental music is excellent for improving attention and reasoning (Ahmad & Rana, 2015;Nadon et al, 2021). Moreover, familiar music is also associated with increased enjoyment and performance on cognitive tasks (Ahmad & Rana, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For example, fast and loud music can impair reading comprehension, while baroque instrumental music is excellent for improving attention and reasoning (Ahmad & Rana, 2015;Nadon et al, 2021). Moreover, familiar music is also associated with increased enjoyment and performance on cognitive tasks (Ahmad & Rana, 2015). Overall, music can be used as a useful tool to improve cognitive performance, but the type of music and its characteristics should be carefully considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmad & Rana in their study observed that people think that they can take themselves out from sadness and sorrow by listening to music. They also posited that music refreshes the soul and keeps our mood high, people love listening to music and enjoy it [5].…”
Section: Conceptual Clarifications 31 Music and The Human Soulmentioning
confidence: 99%